Lipids and pigment-protein complexes of photosynthetic apparatus of Deschampsia antarctica Desv. plants under UV-B radiation - Taran, N.Yu.; Storozhenko, V.O.; Svietlova, N.B.; Topchiy, N.M. (Вiopolymers and Cell, 2012)
Aim. To investigate structural and functional modifications of major components of photosynthetic membranes of endemic antarctic species D. antarctica under UV-B radiation. Methods. For quantitative determination of photosynthetic membrane components we used Arnon’s method (for chlorophylls and carotenoids); separation of carotenoids was carried out by Merzlyak’s method; polar lipids were isolated by Zill and Harmon method in modification of Yakovenko and Mihno; glycolipids separation and identification we carried out by Yamamoto method; and sulfoquinovosyl diacylglycerol content was determined by Kean method. The separation, disintegration and determination of pigment-protein complexes of chloroplasts were carried out by Anderson method. Authenticity of differences between the mean arithmetic values of indices was set after the Student criterion. Differences were considered as reliable at p 0.05. Results. We determined structural and functional changes in lipids, carotenoids and pigment-protein complexes at the photosyntetic apparatus level in D. antarctica plants under UV-B radiation. Conclusions. Adaptation of D. antarctica plants to UV-B radiation is accompanied by a cascade of physiological and biochemical rearrangements at the level of photosynthetic apparatus, manifested as the changes in pigment, lipid and pigment-protein complexes content. Мета. Дослідження структурних і функціональних модифікацій головних компонентів фотосинтетичних мембран ендемічного антарктичного виду D. antarctica за умов жорсткого ультрафіолетового випромінювання. Методи. Кількісне визначення компонентів фотосинтетичних мембран проводили за методом Арнона (для хлорофілів і каротиноїдів), розділення каротиноїдів – за методом Мерзляка, виділення полярних ліпідів – за методом Зілла і Хармона з модифікацією Яковенка і Міхно, розділення гліколіпідів та їхня ідентифікація – за методом Ямамото, а їхній аналіз – за допомогою програми «Total lab», вміст сульфохіновозилдіацилгліцеролу визначали за методом Кіна. Розділення і визначення комплексів пігмент-білок хлоропластів здійснювали методом Андерсон. Достовірність різниці між значеннями середнього арифметичного знаходили за критерієм Ст’юдента. Різницю вважали достовірною при значенні р 0,05. Результати. Встановлено структурні та функціональні зміни ліпідів, каротиноїдів і комплексів пігмент-білок на рівні фотосинтетичного апарату у рослин D. antarctica за умов УФ-В випромінювання. Висновки. Адаптація рослин D. antarctica до впливу жорсткого ультрафіолетового випромінювання супроводжується каскадом фізіологічних і біохімічних перебудов на рівні фотосинтетичного апарату, пов’язаних зі змінами вмісту пігментів, ліпідів і комплексів пігмент-білок. Цель. Исследование структурных и функциональных модификаций главных компонентов фотосинтетических мембран эндемического антарктического вида D. antarctica в условиях жесткого ультрафиолетового излучения. Методы. Количественное определение главных компонентов фотосинтетических мембран проведено по методу Арнона (для хлорофиллов и каротиноидов), разделение каротиноидов – по методу Мерзляка, выделение полярных липидов – по методу Зилла и Хармона с модификацией Яковенко и Михно, разделение гликолипидов и их идентификация – по методу Ямамото, а их анализ – с помощью программы «Total lab», содержание сульфохиновозилдиацилглицерола определяли по методу Кина. Разделение и определение комплексов пигмент-белок хлоропластов осуществляли методом Андерсон. Достоверность различий между значениями среднего арифметического находили по критерию Стьюдента. Различия считали достоверными при значении р 0,05. Результаты. Установлены структурные и функциональные изменения в содержании и соотношении липидов, каротиноидов и комплексов пигмент-белок на уровне фотосинтетического аппарата растений D. antarctica в условиях УФ-В излучения. Выводы. Адаптация растений D. antarctica к воздействию жесткого ультрафиолетового излучения связана с каскадом физиологических и биохимических перестроек на уровне фотосинтетического аппарата, связанных с изменениями в содержании пигментов, липидов и комплексов пигмент-белок.